E23K variant in KCNJ11 gene is associated with susceptibility to type 2 diabetes in the Mauritanian population - Abdelhamid, Isselmou (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2014)
Many genetic association studies reported the contribution of KCNJ11 gene to type 2 diabetes susceptibility in different populations. We aimed to evaluate the association between E23K variant of KCNJ11 and type 2 diabetes in the Mauritanian population.